The historical essay of the department of Pathological Physiology of Dnepropetrovsk Medical Academy. - Kozlova, Yu. V.; Dovgal, M. A.; Koldunov, V. V.; Silkina, Yu. V.; Klopotskiy, G. A.; Khudyakov, A. E.; Khmel, S. I.; Bibikova, V. N.; Tryasak, N. S.; Anisimova, O. V. (Medicni Perspektivi, 2017)
The article presents historical information about the development of the department of Pathological Physiology of Dnepropetrovsk medical academy, about chiefs of the department and their contribution to the development of the department from its foundation (1918) up to the present (2016). The areas of scientific research, the most significant achievements as well as changes in the provision of educational process are described.